DEVELOPMENT OF TOURISM VILLAGES THROUGH BUSINESS MODEL CANVAS IN AN EFFORT TO ATTRACT THE INTEREST OF TOURISTS IN SEMANGAT VILLAGE BARUSJAHE DISTRICT, KARO DISTRICT: - Beby Kendida Hasibuan; Gustanto; Muhammad Anggia Muchtar (RADJA PUBLIKA, 2024)
Tourism continues to grow in Indonesia because it creates jobs, increases welfare and increases regional income. The tourism community for sustainable rural development is accelerated by the tourism sector. Tourism villages utilize existing community potential to empower the community and improve their welfare. Tourism villages reflect the natural richness of the countryside and the socio-economic and cultural situation. Rural tourism encourages villages to preserve culture and nature to attract tourists. Local and foreign tourists know this Karo Regency tourist spot. Karo Regency offers natural, artistic, cultural and historical tourism. Barusjahe District, Karo Regency has Roh Village. Roh Village has natural hot springs that flow directly from springs with the potential for plantations and medicinal plants to be used for agrotourism. All community facilities and infrastructure are complete, but need maintenance and development. Activities that have been carried out include socialization regarding increasing tourist interest in Spirit Village, Barusjahe District, Karo Regency.